Reformulation of Sanctioning Mining Acts of Individual Legal Subjects as Efforts to Improve Ecological Stability in Indonesia - Ismawati Septiningsih (Jurnal Dinamika Hukum, 2021)
This research analyzes the urgency of the need for reformulation of individual legal subjects who commit mining crimes to encourage increased ecological stability in Indonesia. This research is normative legal research using secondary data sources through a prescriptive literature study. The results showed that the frequency of mining criminal acts committed by individual legal subjects has a high rate of cases; it also has implications for the ecological balance around the mining area. The reformulation of sanctions on particular legal matters focuses on changing the substance of articles in Law Number 4 of 2009 concerning Mineral and Coal Mining (Mining Law). In the research, it will be presented with recommendations for changes in the substance of the Mining Law article which regulates the sanction of individual legal subjects who commit mining crimes to create a deterrent effect to the perpetrators, so that in the future it is expected to encourage increased ecological stability in Indonesia through reducing the frequency of criminal cases mining.Keywords: Reformulation; Individual Legal Subjects; Mining Crimes; Mining Law; Ecology.